2014
DOI: 10.1007/s12544-014-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Are young drivers as careful as they deem? In vehicle data recorders and self reports evaluations

Abstract: Purpose This paper aims to explore the driving behavior of young drivers few years after licensure based on two different evaluation approaches, which are used in a complementary manner. The evaluation was done with respect to driving exposure and trip safety. Methods The evaluation is based on two data collection approaches, which were compiled for the same trips: The first, In Vehicle Data Recorders (IVDR), which were installed in the young drivers' vehicles for a study period of 8 months. The second, Self-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…For example, while ∼10% of the participants reported that their total weekly driving time was <2 h, the monitoring data showed >50%; this trend was reversed while ∼20% of the participants reported that their total weekly driving time was >4 h, whereas the monitoring data showed <5%. These findings are in line with results from other studies comparing self-report data with naturalistic data which revealed over-estimation of exposure time compared to objective measures (see for example [23] and the references there).…”
Section: Trips Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…For example, while ∼10% of the participants reported that their total weekly driving time was <2 h, the monitoring data showed >50%; this trend was reversed while ∼20% of the participants reported that their total weekly driving time was >4 h, whereas the monitoring data showed <5%. These findings are in line with results from other studies comparing self-report data with naturalistic data which revealed over-estimation of exposure time compared to objective measures (see for example [23] and the references there).…”
Section: Trips Characteristicssupporting
confidence: 92%
“…These statistics regarding driving patterns and trip characteristics agree with figures reported from other naturalistic studies which dealt with young drivers in Israel [23,24]. Comparing these findings to the self-reported travel times yield that the young drivers significantly over estimated their driving exposure.…”
Section: Trips Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, Huebner et al (2006) found discrepancies between older drivers' self-reported distance travelled with data extracted from an in-vehicle "CarChip". A more recent study examining driving behaviour of young adults found similar discrepancies in self-reports and in-vehicle GPS data with the latter revealing drivers had engaged in more risky behaviours than their self-reports had suggested (Albert et al 2014). …”
Section: Objective Driving Measures Of Persuasive Outcomesmentioning
confidence: 73%
“…Increasingly within the traffic psychology literature, studies are comparing on-road behavioural data obtained from GPS devices with self-reports of one's driving-related behaviour/s (e.g., Albert et al 2014;Blanchard et al 2010;Molnar et al 2013;Huebner et al 2006;Marshall et al 2007). Blanchard et al (2010), for example, reported that GPS devices provided a more reliable measure of the number of driving trips and stops compared with participants' self-reports.…”
Section: Objective Driving Measures Of Persuasive Outcomesmentioning
confidence: 99%